The Effect of Using Quizizz Learning Media on Student Learning Outcomes in Local Content Subjects for Class X TKJ at Private Vocational Schools in Jambi, Medan, Academic Year 2025/2026 - Tamba, Josua; Hasibuan, Novita Indah (Continuous Education: Journal of Science and Research, 2025)
This study attempts to determine the effect of using interactive learning media Quizizz on student learning achievement in Local Content subjects at SMK Swasta X TKJ Jambi Medan in the 2025/2026 academic year. This study was motivated by the low performance results of students who were below the Minimum Completion Criteria (KKM) and low student participation due to the still dominant conventional learning methods. Quantitative methods were used with a quasi-experimental design for this study. The study population was all 64 students of class X TKJ who were divided into control and experimental groups. Pretest and posttest data collection used multiple choice tools. Data analysis used the Mann-Whitney Test to measure significant differences between groups that used Quizizz media and those that did not use Quizizz media. The results showed that there were differences in student learning outcomes between the control and experimental groups. Thus, the use of Quizizz learning media successfully improved student learning outcomes in Local Content subjects. The use of technology-based interactive learning media is recommended by this study as a method to increase student engagement and learning outcomes.